Literature Review: Tren Penelitian Kemampuan Berpikir Kritis Siswa SMA untuk Periode 2020-2025 - Intan Nurul Fitriana; Bambang Subali (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Critical thinking skills are one of the key competencies of the 21st century that high school students need to have to face global challenges and information complexity. This study aims to review the development trends of critical thinking in ASEAN countries during the period 2020–2025. The research method used Systematic Literature Review (SLR). Data was obtained from the Scopus and Google Scholar databases using Publish or Perish software. Out of the 700 articles found, 65 articles were selected based on topic relevance. Content and bibliometric analysis is carried out with the help of VOSviewer through three visualizations: network, overlay, and density. The results showed a significant increase in publications related to critical thinking skills during the study period with 92.3% published in scientific journals and 7.7% in proceedings. Based on country of origin, Indonesia is the largest contributor, followed by Malaysia, the Philippines, Thailand, and Singapore, showing great concern for the development of critical thinking skills in the ASEAN region. These findings provide an overview of the direction of research and the potential to strengthen learning strategies that support the development of critical thinking skills at the upper secondary level.